PENGARUH VIDEO ANIMASI BERBASIS POP UP TERHADAP PENINGKATAN PENGETAHUAN SANTRI KELAS VIII TENTANG PENCEGAHAN PENYAKIT SCABIES (Jurnal Kesehatan Siliwangi, 2021)
According to the 2016 Ministry of Health, the prevalence of scabies in Indonesia is 5.60-12.95% and scabies ranks third of the 12 most common skin diseases in Indonesia. One of the places that have the potential to experience scabies cases is Islamic boarding schools, in Indonesia there are 14,798 Islamic boarding schools with a fairly high prevalence of scabies (Kemenkes RI 2016). Scabies disease generally attacks individuals who live in groups such as Islamic boarding schools. The use of Pop Up -Based Animation Video is one of the promotive efforts to increase students' knowledge in preventing scabies disease. The purpose of the study was to find out the effect of using the media and the effect of Pop Up Based Animation Video on the knowledge of class VIII students about preventing scabies. This type of research uses a pre-experimental design with a One Group Pretest-Posttest Design without Control. The research location is at the Darusyifa Al Fitrat Islamic Boarding School, Sukabumi Regency with the research subjects being students of class VIII at SMPIT Yaspida. The population in this study amounted to 580 students with 101 samples determined through the Random Sampling technique. The results showed an increase in the average knowledge of students by 29.14%. Based on the paired t test, the p-value is 0.00 <0.05. The conclusion of this study is that the use of Pop Up -Based Animation Videos has a significant effect on increasing students' knowledge about scabies prevention at Darusyifa Al Fitrat Islamic Boarding School, Sukabumi Regency. This media can be used as an alternative media to educate students about the prevention of scabies